Transição de fase quântica e modelos de spins frustrados - Azevedo, José Roberto Viana (Universidade Federal de São Carlos, 2007)
In this thesis, we will study the quantum phase transition of frustrated quantum spin models: (i) van Hemmen model ( S = 1) with transverse and anisotropic biaxial field (ii) Heisenberg model (S = 1/2 ) with competitive interaction first and second nearest neighbours (J1-J2 model) (iii) Ising model with transverse field and first magnetic model is studied to simulate the spin glass properties in real systems like the magnetic susceptibility cusp. We use the bimodal and gaussian probability distribution for random interactions. Applying the first-order approximation to decouple the products of exponential of operators, we calculate free energy and order parameter. Both, the transverse field and anisotropic transverse field destroy the spin glass order. In the second model, we use the effective field theory with differential operator technique and effective field renormalization group (EFRG) formalism. The phase diagrams are determined where are observe ferromagnetic (F), antiferromagnetic (AF) and superantiferromagnetic (SAF) states. In case of Heisenberg model in a square lattice at T=0, we have a quantum paramagnetic state that has been considered as a spin-liquid (SL) state in literature. For a simple cubic lattice, this spin-liquid state has not been observed. Which shows that the dimension of the system has influences on the quantum fluctuation at T=0. In the phase diagrams are the presence of first and second order phase transitions. Finally, are consider the critical behavior of the frustrated quantum Ising model and at T=0 we have the states with energy gap proportional to the transverse field intensity. Depending in the frustration parameter the system also shows first and second order transitions.
Keywords: Transição de fase quântica; Modelos de spins quânticos frustrados; CIENCIAS EXATAS E DA TERRA::FISICA